WHAT TO DO WITH HAZARDOUS WASTE? - Loayza P., Jorge (2006)
Hazardous wastes include those materials due to their corrosive, reactive, explosive, toxic, flammable or biohazard characteristics, pose a risk to human health and the environment when handled improperly. The type of treatment depends on the characteristics of the waste. The most commonly used treatments are physical, chemical. biological and thermal. Treatment processes also generate waste, which must be deposited in a special landfill or security deposit.